Conjunctive Water Management for Agriculture With Groundwater Salinity. Issue 10 (29th September 2022) - Yao, Yiqing; Lund, Jay R.; Harter, Thomas
Abstract: Salt accumulations in aquifers significantly affect and transform the conjunctive use of surface water and groundwater supporting irrigated agriculture. Salt accumulates in aquifers under many semi‐arid irrigated lands where pumping has lowered water levels enough to prevent drainage of saline groundwater from the basin. This paper provides new insights into optimal conjunctive management of groundwater pumping, recharge, surface water, and cropping patterns with groundwater salinity and hydrologic variability in an irrigated semi‐arid region, such as California's western San Joaquin Valley, reducing agricultural crop yields and revenues. A two‐stage stochastic quadratic model explores this problem to prescribe economically optimal crop mix and conjunctive water operation policies over a 10‐year period with probabilistic annual surface water availability, considering groundwater salinity's harm to crop yields. At low groundwater salinity, agricultural conjunctive use usually pumps most groundwater in drier years, supplied by additional recharge in wetter years. In contrast, at higher groundwater salinity, optimal conjunctive use pumps less in drier years while pumping more in wetter years, when more surface water allows more dilution of saltier groundwater. Reduced pumping in drier years substantially reduces a region's ability to support higher‐value perennial crops and reduces or eliminates lower‐value annual crops in dry years. Artificial recharge with fresh surface water in wetter years can have economic value from slowing groundwater salination which allows more groundwater use in drier years. Key Points: A two‐stage stochastic quadratic model estimates the economic impact of groundwater salinity on agriculture, especially with perennial crops Economically optimized groundwater management fundamentally changes with groundwater salination Artificial recharge for aquifers with severe salt accumulation can reduce both loss of agricultural production and groundwater salinity